Optimizing model training for speech recognition - Chak, Hui Ping (2010)
Modern speech recognition systems are generally based on statistical models which output a sequence of symbols or quantities. These models can be trained automatically and are simple and computationally feasible to use. To reduce long computational time, the model training can be distributed to many machines for parallel processing. Apache Hadoop is a Java software framework that uses the Map-Reduce architecture to support data-intensive parallel and distributed processing.